PEMBAHARUAN HUKUM ISLAM: - Jamal Ma’mur (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
In the globalization Era, Islamic law reformation is needed to respond actively the changes happened to keep the relevances of Islamic law. Social fiqh (Fiqh Sosial) that was initiated by MA. Sahal Mahfudh is a new paradigm in Islamic law to give the solution to the real problems at the society. Among the social fiqh principles is the verification which teaching included into prime (ushul) and which one into branch (furu‘). This research is law research. There are primary source of data, those are MA. Sahal Mahfudh works, and the secondary data are the supporting works. The theoretical framework applied is the Islamic law reformation. The approaches used are ideology and sociologies approaches.